INTERNALIZATION OF WASATHIYAH VALUES AMONG STUDENTS OF THE KUMPEH DAARU AT-TAUHID ISLAMIC BOARDING SCHOOL IN JAMBI - Chafis, M. Chairul; Zuhdi, Zaenu; A.Qomarudin (Four Son Scholarship, 2026)
This research is motivated by the importance of Islamic boarding school education in shaping the character of students (students), particularly through the internalization of wasathiyah values. These values ??are highly relevant in the context of diverse Indonesia because they foster a tolerant, just, and balanced attitude, while also serving as a solution to counter the increasingly worrying rise of radicalism. This study aims to explore and analyze the process of internalization of wasathiyah values ??among students at the Kumpeh Daaru At-Tauhid Islamic Boarding School in Jambi. Wasathiyah values, which refer to the principles of moderation and balance in Islam, are considered crucial in shaping the character and behavior of students who are tolerant, just, and balanced. The research method used was a qualitative approach, with data collection techniques through observation, in-depth interviews, and documentation. This research employed a qualitative approach with a field study. Data were collected through observation, in-depth interviews, and documentation, then analyzed using an interactive model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the internalization of wasathiyah values ??is carried out through various daily activities at the Islamic boarding school, such as direct teaching, the role model of the ustadz, and special character development programs. The results of the study indicate (1) The wasathiyah values ??internalized by students at the Kumpeh Daaru At-Tauhid Islamic Boarding School in Jambi include the values ??of tawassuth (moderation), tawazun (balance), i'tidal (justice), tasamuh (tolerance), musyawarah (deliberation), and islah (peace). (2) The stages of internalization of wasathiyah values ??are: First, planning (Planning) Internalization of Wasathiyah Values, the Islamic boarding school has formulated core wasathiyah values ??such as tolerance, justice, balance, and love of peace which are then integrated into the curriculum, extracurricular activities, and student development programs. Second, Implementation of Internalization of Wasathiyah Values, realized through the example of teachers and caregivers who are the main figures for students. Third, Evaluation of Internalization of Wasathiyah Values, teachers and caregivers monitor students in various activities. (3) The results of internalization of Wasathiyah values ??are seen in changes in the attitudes and characters of students, including: students become more moderate in their behavior, do not judge easily, are able to live side by side peacefully in a pluralistic society, and become agents of change who spread the values ??of tolerance, justice, and balance in social and religious life.